2011
DOI: 10.1523/jneurosci.5758-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Neuroimaging of Voluntary Audiospatial Attention: Evidence for a Supramodal Attention Control Network

Abstract: Previous attempts to investigate the supramodal nature of attentional control have focused primarily on identifying neuroanatomical overlap in the frontoparietal systems activated during voluntary shifts of spatial attention in different sensory modalities. However, the activation of the same neural structures is insufficient evidence for a supramodal system, as the same brain regions could interact with one another in very different ways during shifts of attention in different modalities. Thus, to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 31 publications
7
35
0
Order By: Relevance
“…To our knowledge, this is the first study to unequivocally demonstrate target-specific high gamma power increases in this region of non-primary auditory cortex through examination of ECoG recorded directly from PLST. Previous studies have demonstrated high gamma power increases to attended versus non-attended sounds in selective attention tasks (e.g., Green et al, 2011; Doesburg et al, 2012; Mesgarani and Chang, 2012), and we found a similar effect when comparing high gamma activity acquired during attended versus passive listening blocks (subject L237). In contrast to previous studies, however, we identify additional specific effects restricted to target stimuli.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the first study to unequivocally demonstrate target-specific high gamma power increases in this region of non-primary auditory cortex through examination of ECoG recorded directly from PLST. Previous studies have demonstrated high gamma power increases to attended versus non-attended sounds in selective attention tasks (e.g., Green et al, 2011; Doesburg et al, 2012; Mesgarani and Chang, 2012), and we found a similar effect when comparing high gamma activity acquired during attended versus passive listening blocks (subject L237). In contrast to previous studies, however, we identify additional specific effects restricted to target stimuli.…”
Section: Discussionsupporting
confidence: 83%
“…The results of our brain source analyses indicate coactivation in both parietal (at junction with associative occipital and temporal cortices) and prefrontal structures along with sensory structures during attend and ignore effects. These associate regions resemble the supramodal network that has been reported to guide attention to operate across attended modalities (Green, Doesburg, Ward, & McDonald, 2011; Green & McDonald, 2008; Driver, Eimer, Macaluso, & Van Velzen, 2003; Eimer, van Velzen, Forster, & Driver, 2003). …”
Section: Discussionmentioning
confidence: 84%
“…A top–down, attentional modulation of the neural activity in PSCs is not a likely explanation for the correct classification of the responses elicited by non-principal stimuli, because the attentional effects triggered by stimuli of different sensory modalities are not expected to modulate the activity within non-corresponding PSCs in a spatially distinct manner353637. Indeed, a number of studies have shown that stimuli of different modalities activate a single supramodal attentional control network3536, and it is unlikely that its possible top–down modulatory effect on PSCs is spatially different for different sensory modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of studies have shown that stimuli of different modalities activate a single supramodal attentional control network3536, and it is unlikely that its possible top–down modulatory effect on PSCs is spatially different for different sensory modalities. The lack of correlation between the differences in subjective ratings of stimulus saliency and two-way classification accuracies also suggests that these were not driven by differences in attentional re-orientation or arousal.…”
Section: Discussionmentioning
confidence: 99%